Mıcrobıal straın ımprovement strategıes for levan productıon - Erkorkmaz, Burak Adnan (My University, 2017)
Levan üstün özellikleri sebebi ile endüstriyel olarak önemli bir fruktan polimeridir. ABSTRACT Levan is an industrially important fructan polymer with its distinguished properties, however its high production cost is the biggest bottleneck that need to be overcome by innovative approaches affording highly productive microbial production systems.
Keywords: Biyomühendislik; Biyoteknoloji; Levan; Levan Levan; Teknikler; Üretim